PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DAN TGT PADA PEMBELAJARAN GEOGRAFI TERHADAP HASIL BELAJAR KELAS XI IPS DI SMAN 11 TEBO, JAMBI. - Alim, Roki Nur; Mariya, Sri (JURNAL BUANA, 2024)
This research was conducted to determine the effect of applying the TGT model and STAD model to the learning outcomes of students at SMAN 11 Tebo, Jambi. The approach used is a quarsi experiment with a pretest-posttest nonequivalent control design. The samples taken in this study were 60 students using a random sampling technique in class XI IPS 1 and class XI IPS 2. The data analysis method used in this study was carried out with the help of Microsoft Excel and SPSS 26 applications. Data collection techniques were in the form of documentation, tests learning outcomes, and questionnaires. From processing the results of the posttest experimental class, the average learning result is quite high, namely 72 compared to the control class with an average learning result of 66. For the N-gain test, students in the experimental class get a percentage of 56% (quite effective) while in the control class only get a percentage of 51% (less effective). So that in this study there was a positive influence from the application of the STAD type cooperative learning model by contributing 40.5% to increasing the learning outcomes of class XI IPS students at SMAN 11 Tebo, Jambi.